A randomised controlled trial comparing transnasal humidified rapid insufflation ventilatory exchange (THRIVE) pre‐oxygenation with facemask pre‐oxygenation in patients undergoing rapid sequence induction of anaesthesia 1. (30th December 2016) - Mir, F.; Patel, A.; Iqbal, R.; Cecconi, M.; Nouraei, S. A. R.
Summary: Pre‐oxygenation is an essential part of rapid sequence induction of general anaesthesia for emergency surgery, in order to increase the oxygen reservoir in the lungs. We performed a randomised controlled trial of transnasal humidified rapid insufflation ventilatory exchange (THRIVE) pre‐oxygenation or facemask pre‐oxygenation in patients undergoing emergency surgery. Twenty patients were allocated to each group. No patient developed arterial oxygen saturation < 90% during attempted tracheal intubation. Arterial blood gases were sampled from an arterial catheter immediately after intubation. The mean (SD) PaO2 was 43.7 (15.2) kPa in the THRIVE group vs. 41.9 (16.2) kPa in the facemask group (p = 0.722); PaCO2 was 5.8 (1.1) kPa in the THRIVE group vs. 5.6 (1.0) kPa in the facemask group (p = 0.631); arterial pH was 7.36 (0.05) in the THRIVE group vs. 7.34 (0.06) in the facemask group (p = 0.447). No airway rescue manoeuvres were needed, and there were no differences in the number of laryngoscopy attempts between the groups. In spite of this, patients in the THRIVE group had a significantly longer apnoea time of 248 (71) s compared with 123 (55) s in the facemask group (p < 0.001). Transnasal humidified rapid insufflation ventilatory exchange is a practicable method for pre‐oxygenating patients during rapid sequence induction of general anaesthesia for emergency surgery; we found that it maintained an equivalent blood gas profile to facemask pre‐oxygenation, in spite of a significantly longer apnoea time.